The influence of prepaid service and promotion purchase restriction on consumers’ willingness to share in tourism and hospitality: from the perspective of framing effect theory - Luo, Haohan; Pan, Ningning; Zhong, Yalin; Wang, Haijun (Frontiers in Psychology, 2022)
Prepaid service is not only a financial tool, but also a common promotion mode in tourism and hospitality. Due to the limited resources of the enterprise, the enterprise needs to reasonably allocate the promotion resources to maximize the effectiveness of the promotion. As two common promotion purchase restrictions, limited-time promotion and limited-quantity promotion how to interact with prepaid services in the form of discounts or freebies to enhance consumers' willingness to share is the focus of this study. This study carried out three experiments based on framing effect theory, stimulus-organism-response theory, and social capital theory, which has found that the prepaid service mode moderates the relationship between promotion purchase restrictions and consumers' willingness to share. When the prepaid service mode is a discount type, the limited-quantity promotion can generate higher sharing willingness than the limited-time promotion, and the perceived scarcity plays a mediating role. When the prepaid service mode is a freebie type, the limited-time promotion can generate higher sharing willingness than the limited-quantity promotion, and the perceived certainty of opportunity plays a mediating role.